Back Cover: Copper Nitrate Mediated Regioselective [2+2+1] Cyclization of Alkynes with Alkenes: A Cascade Approach to Δ2‐Isoxazolines (Angew. Chem. Int. Ed. 30/2015). Issue 30 (25th June 2015) - Gao, Mingchun; Li, Yingying; Gan, Yuansheng; Xu, Bin
<x xml:space="preserve">Abstract</x> Copper nitrate trihydrate is employed as a novel precursor of nitrile oxides. In their Communication on page 8795 ff., B. Xu and co‐workers describe an efficient copper nitrate mediated cascade reaction of simple alkynes and alkenes that selectively leads to pharmacologically interesting polysubstituted Δ2‐isoxazolines under mild conditions.